Psychrobacillus glaciei sp. Nov., a psychrotolerant species isolated from an antarctic iceberg - Choi, Jun Young; Lee, Pyung Cheon (International Journal of Systematic and Evolutionary Microbiology, 2020)
We performed taxonomic studies on a psychrotolerant strain, designated PB01T, isolated from an Antarctic iceberg. The cells of strain PB01T were Gram-stain-positive, strictly aerobic, white–yellow and rod-shaped. The results of 16S rRNA gene sequence analysis revealed that strain PB01T was closely related to Psychrobacillus psychrodurans DSM 11713T (99.19% similarity), Psy-chrobacillus psychrotolerans DSM 11706T (98.91%) and Psychrobacillus insolitus DSM 5T (98.85%). Despite high 16S rRNA gene sequence similarity, the degrees of DNA–DNA relatedness between strain PB01 T and its three closest phylogenetic neighbours were 62.4±7.3 % for P. psychrodurans DSM 11713T, 61.1±5.4 % for P. psychrotolerans DSM 11706T and 56.1±6.9 % for P. insolitus DSM 5T. The predominant cellular fatty acids were anteiso-C15: 0, iso-C15: 0 and C16: 1ω7с-OH. Menaquinone-8 was the major respiratory quinone, and phosphatidylethanolamine was the major polar lipid. The DNA G+C content of strain PB01T calculated from the complete genome sequence was 36.0 mol%. Based on the phenotypic, chemotaxonomic, genomic and phylogenetic data obtained in the present study, we conclude that strain PB01T represents a novel species of the genus Psychrobacillus, for which we propose the name Psychrobacillus glaciei sp. nov. The type strain is PB01T (=CECT 9792T=KCTC 43041T).
Keywords: Antarctic Regions; Bacillaceae; Bacterial Typing Techniques; Base Composition; DNA, Bacterial; Fatty Acids; Ice Cover; Phosphatidylethanolamines; Phylogeny; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Vitamin K 2; Antarctica; Iceberg; Psychrobacillus